Reform Ideals and Teachers’ Practical Intentions - Kennedy, Mary M. (Education Policy Analysis Archives, 2004)
Reformers have been trying for decades to alter the fundamental character of classroom instruction in the United States, but have repeatedly been unsuccessful in fostering significant change in teaching practice. Several hypotheses have been put forward to account for this problem–that teachers lack sufficient knowledge (hence we need more professional development), that they lack sufficient will (hence we need accountability systems) or that they disagree with reform ideals or find other agendas to be more compelling in their classrooms. This paper addresses the third hypothesis by trying to ascertain what teachers care about when they respond to specific classroom situations. Numerous authors have suggested that teachers’ beliefs, values, and perceptions influence their practices, but most papers in this area focus on just one teacher or a small handful of teachers and show how these particular teachers’ ideas influence their practice. We still have little idea what kinds of concerns and intentions tend to be pervasive in teachers’ thinking, and how these ideas differ from those embodied in reform ideals. The paper begins by reviewing reform literature and outlining its main themes. It then describes a study of teachers’ interpretations of classroom situations and their intentions for specific things they did in those situations. From teachers’ discussions of their practices, the author identifies the primary areas of concern that dominated teachers’ thinking as they constructed their practices and shows where these concerns are similar to, and different from, reform ideals.